2015
DOI: 10.1155/2015/927105
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Administration of Bortezomib in Combination with Thalidomide and Dexamethasone for Treatment of Newly Diagnosed Multiple Myeloma Patients

Abstract: Objective. To investigate the efficacy and safety of the treatment of the newly diagnosed multiple myeloma (MM) patients with the therapy of subcutaneous (subQ) administration of bortezomib and dexamethasone plus thalidomide (VTD) regimen. Methods. A total of 60 newly diagnosed MM patients were analyzed. 30 patients received improved VTD regimen (improved VTD group) with the subQ injection of bortezomib and the other 30 patients received conventional VTD regimen (VTD group).The efficacy and safety of two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
9
1
Order By: Relevance
“…In a meta‐analysis evaluating TVD, Leiba et al found a postinduction VGPR rate (or better) around 60%, compared to 75% in our study. Moreover, the median PFS is higher with the RVD combination (45 months in our work) than with TVD (range: 18.3‐33.1 months) . These results are similar to those found by Rosiñol et al in their integrated analysis of randomized clinical trials evaluating RVD or TVD: Responses were deeper with RVD than TVD (≥ VGPR rate after induction with VRD vs VTD was 66.3% vs 51.2%; P = .00281).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a meta‐analysis evaluating TVD, Leiba et al found a postinduction VGPR rate (or better) around 60%, compared to 75% in our study. Moreover, the median PFS is higher with the RVD combination (45 months in our work) than with TVD (range: 18.3‐33.1 months) . These results are similar to those found by Rosiñol et al in their integrated analysis of randomized clinical trials evaluating RVD or TVD: Responses were deeper with RVD than TVD (≥ VGPR rate after induction with VRD vs VTD was 66.3% vs 51.2%; P = .00281).…”
Section: Discussionsupporting
confidence: 90%
“…The incidence of thalidomide‐related neuropathy (all grades) varies between 10% and 83% . With TVD combination, the risk of peripheral neuropathy ≥grade 3 is about 10 to 31%, in comparison with our 5% rate with RVD combination. This rate of peripheral neuropathy ≥grade 3 related to RVD was similar to the rate found by Rosiñol et al comparing RVD and TVD (5% versus 15.4%) .…”
Section: Discussioncontrasting
confidence: 51%
“…These outcomes were subsequently confirmed in the randomized, prospective MMY-3021 study involving RRMM patients 1113 which led to the 2012 approval of SC Btz in the United States and European Union. However, despite several other reports supporting the use of SC Btz, 14, 15 , there is very limited data available about the safety and efficacy profile of SC Btz in Chinese and Asian patients with newly-diagnosed multiple myeloma (NDMM) 1619 . Few studies with small cohorts compared the two administration routes in Asian patients 20, 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The median PFS of subcutaneous injection group and intravenous injection group was 10.2 months and 8 months, respectively ( P > .05), and the 1-year OS rate were 72.6% and 76.7%, respectively ( P > .05). Merz et al, [39] Liu et al, [40] and Wu et al [41] showed better tolerability and similar treatment response of subcutaneous vs intravenous bortezomib. On the other hand, Minarik et al [42] reported similar effectiveness but also similar adverse reactions of subcutaneous and intravenous bortezomib.…”
Section: Discussionmentioning
confidence: 99%